17 Reasons I Love Ellipses in Poetry, Prose, and Translation. - Stefanescu, Alina (World Literature Today)
The article discusses ellipses in poetry, prose, and translation. Topics discussed include the suspense and sound inside silence created by ellipses, translators dealing with physical silence with ellipses citing reference to Susan Bernofsky's translation of the book "Microscripts" by Robert Walser, and ellipses-effusion in an essay by author Ander Monson.